Utilizing Virtual Reality as an Innovative Tool to Improve Teachers' Conflict Management Abilities in Addressing Cyberbullying - Siti Aminah; Ika Kartika (CV. Creative Tugu Pena, 2026)
Cyberbullying has become a critical challenge in educational environments, with 30% of students experiencing victimization while only 23% of teachers report confidence in managing such cases. This research developed, implemented, and evaluated a Virtual Reality (VR)-based training program to enhance teachers' cyberbullying conflict management abilities. Employing a qualitative collective instrumental case study design, the research engaged eight junior high school teachers from four schools in Cibinong, West Java, through a participatory design approach. Data collection utilized methodological triangulation (in-depth interviews, participatory observation, focus group discussions, and reflective journals), analyzed through reflexive thematic analysis. The study identified five critical teacher competency domains: contextual digital literacy, early detection and behavior interpretation, strategic intervention skills, therapeutic communication, and capacity to build support and prevention systems. Five realistic VR scenario categories were developed—early detection, direct intervention, multi-stakeholder communication, victim support, and prevention/education—characterized by contextual authenticity, linguistic nuance, cultural relevance, relational complexity, and ethical ambiguity. Training effectiveness evaluation demonstrated substantial improvements: early detection accuracy increased from 25% to 87%, teacher confidence rose by 62%, and intervention likelihood increased by 57%. Follow-up interviews three months post-training confirmed sustained skill transfer to real classroom situations, with participants reporting systemic shifts from reactive to preventive approaches. Despite proven effectiveness, implementation challenges included technological accessibility constraints and variations in teachers' digital literacy levels. This research contributes the first empirical evidence that immersive VR technology can effectively bridge the theory-practice gap in teacher preparation for technology-mediated conflict management, offering a validated, scalable model for educational institutions worldwide.